Kefir-carrageenan hydrogel beads: optimization of swelling, swelling and release kinetics - Tos, Seyma; Kilic, Dilek; Dogan, Ozlem (SPRINGER, 2026)
In this study, kappa-carrageenan-based hydrogel beads doped with kefir biomass were synthesized and characterized using Fourier-transform infrared spectroscopy (FTIR) and scanning electron microscopy (SEM). A Box-Behnken experimental design was employed to evaluate the effects of the kefir biomass ratio, cross-linker (KCl) concentration, and medium pH on the swelling capacity of the beads. ANOVA results demonstrated that the cross-linker concentration and the interactions between these factors significantly influenced the swelling behavior. Under optimized conditions (15% kefir biomass, 0.5 M KCl, and pH 5.2), a maximum swelling degree of 32.03 gsolution/gbeads was achieved. Furthermore, the beads were loaded with a red food dye as a model drug to investigate their release behavior. Kinetic studies revealed that the swelling process follows a pseudo-first-order model, while the release of the model drug aligns with the Ritger-Peppas mechanism.
Keywords: Hydrogel; Kefir; Carrageenan; Swelling; Optimization; Kinetics; EXTRACTION; PARTICLES; DELIVERY; FILMS; Chemistry; Polymer Science